A low-cost "water-in-salt" electrolyte for a 2.3 V high-rate carbon-based supercapacitor. Issue 13 (12th March 2019) - Bu, Xudong; Su, Lijun; Dou, Qingyun; Lei, Shulai; Yan, Xingbin
Abstract : With the advantages including wide ESW, superior conductivity, low viscosity and low cost, NaClO4 -based WIS electrolyte can be considered as a promising candidate for high-voltage and high-rate aqueous carbon based SCs with good safety. Abstract : Aqueous electrolytes have shown extraordinary promise for safe electrochemical energy storage devices, but their widespread use is severely limited by the narrow electrochemical stability window (ESW). Here we demonstrate the great feasibility of using a superconcentrated sodium perchlorate aqueous solution as a low-cost "water-in-salt" electrolyte to construct a high-performance carbon-based supercapacitor (SC). The attractive features of this electrolyte including wide ESW and excellent conductivity enable the model SC to fully work at 2.3 volts with superior rate capability and outstanding cycling stability. This SC exhibits a comparable energy density, a higher power density and a much lower price compared to commercial non-aqueous SCs working at 2.7 volts, representing significant progress toward practical applications.